2020
DOI: 10.1111/anec.12812
|View full text |Cite
|
Sign up to set email alerts
|

Validation of electrocardiographic criteria for identifying left ventricular dysfunction in patients with previous myocardial infarction

Abstract: Background Eleven criteria correlating electrocardiogram (ECG) findings with reduced left ventricular ejection fraction (LVEF) have been previously published. These have not been compared head‐to‐head in a single study. We studied their value as a screening test to identify patients with reduced LVEF estimated by cardiac magnetic resonance (CMR) imaging. Methods ECGs and CMR from 548 patients (age 61 + 11 years, 79% male) with previous myocardial infarction (MI), from the DETERMINE and PRE‐DETERMINE studies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…On the other hand, our study showed a positive correlation between QRS duration and hospitalization duration, intensive care need, all-cause mortality and cardiac mortality. These findings are in line with the results of previous studies that showed the relationship between QRS duration and both myocardial dysfunction and sudden cardiac death [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, our study showed a positive correlation between QRS duration and hospitalization duration, intensive care need, all-cause mortality and cardiac mortality. These findings are in line with the results of previous studies that showed the relationship between QRS duration and both myocardial dysfunction and sudden cardiac death [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Both ECG and conventional chest radiography are suitable for medical checkups, but limited for assessment of cardiac function. 22,25 Echocardiography is the most commonly used examination used to assess cardiac function, but requires a long examination time and well-trained operators. For this reason, echocardiography is rarely performed at general medical checkups.…”
Section: Future Prospects Of Dcrmentioning
confidence: 99%